Deconstructing Power Relation in An Illustrated Children’s Storybook How Turtle Got His Shell, Why Tiger Can’t Climb Trees - Putra, Jonathan Syah; Nathanael, Jeshua; Paat, Cinzia Pingkan Abigail; Riven, Abednego Rick; Rustandar, Evan Denzel; Wijaya, Josh Fitzkioshi (Yayasan Pendidikan Gereja Masehi Advent Hari Ketujuh Makarios, 2024)
This paper investigates the power relations present in the children's narrative